2008
DOI: 10.2134/jeq2007.0408
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Transport Processes of Nitrogen, Phosphorus, and Herbicides to Streams in Five Agricultural Basins, USA

Abstract: Agricultural chemical transport to surface water and the linkage to other hydrological compartments, principally ground water, was investigated at five watersheds in semiarid to humid climatic settings. Chemical transport was affected by storm water runoff, soil drainage, irrigation, and how streams were linked to shallow ground water systems. Irrigation practices and timing of chemical use greatly affected nutrient and pesticide transport in the semiarid basins. Irrigation with imported water tended to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 30 publications
2
66
0
Order By: Relevance
“…within the Lake Greifensee (Switzerland) epilimnion was 100-200 days (Huntscha et al, 2008). Finally, a similar transport process was responsible for MESA and nitrate-N delivery to streams in several US agricultural watersheds (Domagalski et al, 2008). Thus, because the major metabolite of metolachlor, MESA, is exceptionally stable and soluble, has a low K oc , and is formed in the unsaturated zone where nitrate-N is transported, it is an ideal transport analog for assessing the fate of agricultural nitrate-N.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…within the Lake Greifensee (Switzerland) epilimnion was 100-200 days (Huntscha et al, 2008). Finally, a similar transport process was responsible for MESA and nitrate-N delivery to streams in several US agricultural watersheds (Domagalski et al, 2008). Thus, because the major metabolite of metolachlor, MESA, is exceptionally stable and soluble, has a low K oc , and is formed in the unsaturated zone where nitrate-N is transported, it is an ideal transport analog for assessing the fate of agricultural nitrate-N.…”
Section: Introductionmentioning
confidence: 86%
“…Glutathione conjugation is the common detoxification method for metolachlor in plants (Cole, 1994;Field and Thurman, 1996) and for its microbial degradation pathway in soil unsaturated zones (Aga and Thurman, 2001;Aga et al, 1996;Aly and Schröder, 2008;Domagalski et al, 2008). In both plant and microbial degradation, glutathione-S-transferase mediates glutathione nucleophilic substitution at the chlorinated carbon of metolachlor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The USEPA's TMDLs require states and local governmental agencies to decrease or limit the total loads of contaminants to water bodies from both point and nonpoint sources to achieve water-quality standards (e.g., Delaware Department of Natural Resources and Environmental Control, 1998). Groundwater discharge is the primary source of N to streams on the Delmarva Peninsula, providing as much as 70% of the N flux, predominantly as nitrate (Ator and Denver, 2012;Domagalski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study of tile drain outlets in southwestern Ohio found an average concentration of nitrate-N of 17 mg L -1 was discharged to receiving waters (Fleming et al, 1998). The crop production system employed, the amount, rate, and timing of fertilizer application, the size and arrangement of drainage tiles, and the presence of cover crops are all known to influence nitrogen inputs to surface waters from tile drainage systems (Kaspar et al, 2007;Kladivko et al, 2004;Nangia et al, 2008;deVos et al, 2000;Domagalski et al, 2008;Dinnes et al, 2002). Agronomic controls such as crop and fertilizer management, however, are not usually sufficient to rectify nutrient pollution resulting from tile drainage systems (Jaynes et al, 2008;Madramootro et al, 2007).…”
Section: )mentioning
confidence: 99%